Strategi Guru Pendidikan Agama Islam dalam Pembentukan Karakter Peserta Didik Kelas X di SMK Negeri 3 Gowa - Nurhasibah, St; Mustamin, Mustamin; Wahab, Abdul; Burhanuddin, Muh Azhar; A. Natsir, Andi Fadhillah (Journal of Gurutta Education, 2025)
This research is motivated by the importance of character education in shaping students' personalities based on Islamic values. The aim of this study is to identify the strategies employed by Islamic Religious Education (PAI) teachers in shaping the character of Grade X students at SMK Negeri 3 Gowa, as well as to determine the supporting and inhibiting factors in its implementation. This study employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation to gain in-depth information regarding the character-building strategies applied by PAI teachers. The findings reveal that the strategies used include delivering advice, modelling good behaviour, habituation, mentoring, and providing educational sanctions. These strategies are aimed at fostering a positive environment that encourages students to develop strong moral values and a sense of responsibility. However, the study also identifies several challenges, such as limited resources and varying levels of student engagement, which can hinder the effective implementation of these character-building initiatives. The inhibiting factors include limited instructional time and the lack of awareness among some students. Meanwhile, the supporting factors consist of cooperation between teachers and parents, as well as a school environment that supports character development. The study concludes that character formation is not solely based on delivering religious material but also emphasises exemplary behaviour, effective communication, and the continuous internalisation of moral values. The success of the teacher’s strategy greatly depends on the synergy between Islamic values-based learning approaches and a supportive environment.